A Research for Identifying Study Anxiety Sources among University Students - Awang, Mohd Ghani; Vitasari, Prima; Muhammad Nubli, Abdul Wahab; Othman, Ahmad (Canadian Center of Science and Education, 2010)
University students suffer to some levels of study anxiety, such as; have new experiences, environment and situation. Study anxiety is a real phenomenon. Campus environment has universal access to increase study anxiety among students. The prevalence of study anxiety has been acknowledged by students and educators. However, no current research exists to identify the study anxiety sources among university students. In this research, we present a survey aimed to identify of study anxiety sources among university students. The survey involves 770 students of Universiti Malaysia Pahang. The survey asks students about experiences, feelings and thoughts related with anxieties during study process. The results identify seven sources. But, there are five potential sources of study anxiety; exam anxiety, class presentation anxiety, mathematic anxiety, language anxiety and social anxiety. Descriptive statistics were used to analyze the data which was run in SPSS 16.0. The results will be used to address study anxiety sources among university students. Keywords: Study anxiety sources, University students, Academic performance